Художня інтерпретація феномену характерництва в українському мистецтві XIX – початку XXI століть - Колесник, О.С. (Культура народов Причерноморья, 2013)
Стаття присвячена компаративному аналізу творів, в яких зображується козацьке
характерництво (від «Чорної ради» до «Даогопака»), на основі чого визначаються тенденції художньої
інтерпретації цього феномену. Причини активного звернення українських авторів до цієї теми
пояснюються за допомогою залучення світового контексту, зокрема, «пошуків коренів», характерних
для народів, які стверджують свою ідентичність. Статья посвящена компаративному анализу произведений, в которых изображается
казачье характерничество (от «Черной рады» до «Даогопака»). Причины активного обращения
украинских авторов к этой теме поясняется с привлечением мирового контекста, в частности,
«поисков корней», характерных для народов, утверждающих свою идентичность. In the history of Ukrainian Cossaks there is a well–known but still inadequately explained
phenomenon of “kharakternitstvo”, a kind of battle skill or even battle magic. It has attracted the attention of the
authors of the historical novels, as well as artists, sculptors and film directors since the emergence of Ukrainian
historical genre in mid ХІХ ct. The new interest in the topic, seen in contemporary Ukrainian culture can be
explained as one of the manifestation of the global tendency of “searching for roots”, especially typical for
nations that had the colonial experience. The first writer to tackle the theme was P. Kulish, who presented
“kharakternitstvo” as a popular belief with no exact foundation in reality. In the art of XX and early XXI ct. it is
more often depicted in the way of “magical realism” or historical fantasy. One more tendency is shifting the
focus from Ukrainian–Russian and Ukrainian–Polish relations to the contacts of Ukrainians with the Islamic
nations of the Black Sea region.